СИНТЕЗ ТРИКОНТУРНИХ КІЛ НАПІВПРОВІДНИКОВИХ ЕЛЕКТРОРОЗРЯДНИХ УСТАНОВОК З НАКОПИЧУВАЛЬНИМ КОНДЕНСАТОРОМ - Розискулов, С.С.; Маслак, Л.П.; Перетятко, Ю.В.; Белкін, С.В. (Інститут електродинаміки НАН України, Київ, 2018)
It is shown that if in the three-loop circuits of the capacitors of electric discharge installations (EDI) the charge thyristor is switched on after the end of the previous reverse recharge of the capacitor to a positive voltage, then in the EDI is realized a negative voltage feedback and for the capacitor charge voltage will be satisfied the inequality UC ≤ 2UGDV. If the thyristor VT1 is switched on before the end of the capacitor reverse recharge, it is possible to realize a controllable voltage feedback, which can be either negative or positive, depending on the voltage polarity on the capacitor at the moment of VT1 activation. References 14, figures 4.